A stranger in my own home: Prolonged travel and the (re)negotiation of Otavalo identity in Carlos Arcos Cabrera's Memorias de Andrés Chiliquinga ('Memories of Andrés Chiliquinga') (2013). Issue 1 (1st April 2020) - O'Neil, Megan
As one of Ecuador's largest indigenous groups, Otavalos have become unique in their successful marketing of cultural products both nationally and internationally. The Otavalo diaspora has led to sizeable communities settling not only in larger cities within Ecuador, but around the world. Travel, especially to Europe and the United States, is now a rite of passage for young Otavalos, and these travelling merchants spread their heritage through the sale of products, from clothing and fabrics, to music and handicrafts. In turn, many spend a significant portion of the year (and their life) detached from the Otavalo community, moving through spaces in which they are labelled as 'other' to ones in which they are exclusive members of an 'imagined community'. With a focus on Carlos Arcos Cabrera's 2013 novel Memorias de Andrés Chiliquinga ('Memories of Andrés Chiliquinga'), this article explores the effects of prolonged travel on indigenous identity, and the ways in which the young Otavalos today are facing traditional and Eurocentric stereotypes in order to (re)negotiate what it means to be indigenous in a globalized world.